(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
In creating nations, flooding because of cataclysmic events, for example, tropical storms and seismic tremors brings about enormous death toll and property. Warning people group of the approaching flood gives a successful answer for this by giving individuals adequate time to empty and ensure their property. Be that as it may, the scope of early warning system arrangements presents a tangle of clashing prerequisites including expense and unwavering quality, and makes a few intriguing issues from factors as different as innovative, social, and political. The many-sided quality of these systems and requirement for independence inside the setting of a creating nation while staying viable and open by nontechnical staff gives a test not frequently explained inside created nations, a great deal less the creating. In the wake of portraying this issue, the paper talks about a proposed answer for the issue, beginning tests in executing the arrangement, and lessons learned through that work.